Fra Bøgebjerg til Bispebjerg: Grundtvigskirkens forhistorie - Plaetner, Svea-Yvonne (Kirkehistoriske Samlinger, 1994)
In the article “From Bøgebjerg to Bispebjerg’’ the story is told explaining why there is a church at Bispebjerg in Copenhagen carrying the name of N. F. S. Grundtvig. The events are followed chronologically, from the year 1900, when the Danish sculptor Rasmus Bøgebjerg (1859-1921) made his statue of Grundtvig, until in 1921 the foundation stone of the church was laid down. The statue started a debate among Grundtvigs followers about the need for a memorial. The conflicting points of view led to a power struggle within the movement in which the art became the dividing factor. What was originally planned as a memorial statue became an impressive church. The exact period of debating and building Grundtvig’s Cathedral covers the years from 1900 to 1940, divided into two periods of twenty years each. The temporary tower church was consecrated in 1927 and the whole building project was completed in 1940.